Making A Web-Based Application For Sales Kitchen Bunda Ghina Using Php And Mysql - Adam Huda Nugraha (International Journal of Science, Technology & Management, 2021)
Mother Ghina's kitchen is located in Teluk Low Pasar Village, Tebo Ilir District, Jambi Province. When transacting, store sellers still use simple media for information delivery, such as WhatsApp, Facebook and word of mouth. The purpose of creating this application is to expand promotional media and make it easier for consumers from inside and outside the city to place orders online. In the process of creating the website using PHP programming language and Mysql as database. The final stage is to conduct a trial over the Internet.